Between reproductive rights and access to reproductive healthcare services: narratives of reproductive rights activists in South Africa - Jacobs, Marc (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
The motivation behind the research paper, "Between reproductive rights and access to reproductive healthcare services: Narratives of reproductive rights activists in South Africa" stems from the notion that civil society groups have often played a critical role in addressing social justice issues concerning women's rights. Since 1996 after implementation of the Choice on Termination of Pregnancy (CTOP) Act, South Africa has frequently been praised for its progressive abortion laws that formally recognises women's need for reproductive autonomy and equality. However, ineffective implementation has resulted in many women facing a combination of barriers to accessing reproductive healthcare services. Thus, resulting in some women opting for unsafe, illegal abortion services and placing their health and lives in danger. The purpose of the study, therefore, is to capture the perceptions of contemporary South African based reproductive rights activists and NGOs who engage in campaigns that seek to highlight the complex relationship between reproductive rights and access to such rights. Data for the study was collected through open-ended questionnaires in which participants provided their unique opinions as activists who regularly engage with the abortion and access issues in South Africa. Results from the study suggest that ineffective implementation of the CTOP Act can be attributed to a lack of political will to prioritise women's sexual and reproductive rights, thereby further marginalising women in society. Results also point to the need for widespread support from civil society on women's rights matters so that the State can more effectively be held accountable for catering to the most marginalised women in South African society.
Keywords: Reproductive rights -- South Africa; Reproductive rights -- Political aspects -- South Africa; Human reproduction -- Law and legislation -- South Africa; Reproductive health -- South Africa; Abortion -- Government policy -- South Africa; South Africa. Choice of Termination of Pregnancy Act, 1996